Does Distribution Channel Selection Matter among Zakat-Assisted and Non-Assisted Organic Rice Farmers? An Impact Assessment - Lathifah, Fitriyani; Najib, Mukhamad; Beik, Irfan Syauqi (International Journal of Zakat, 2023)
An organic farming system has the potential to advance farmers’ wealth in comparison to conventional farming, owing to its ethical value factors. This study examines the influence of farmers’ decision-making in choosing a distribution channel on their quality of life. This research samples both farmers who receive financial assistance from the zakat fund and those who do not. This study incorporates the ethical values of Islamic commerce into the model of analysis. The data is obtained from 64 farmers, analyzed using Structural Equation Modeling – Partial Least Squares (SEM–PLS) and independent statistical tests. Four criteria were identified as having a beneficial impact on farmers’ quality of life, however, yielding no evidence to claim any difference in the quality of life between assisted-zakat and non-assisted farmers. The implications of this research are crucial for an appropriate measure of zakat impacts. Nevertheless, a larger sample size is necessary to obtain reliable results. The policy implications are to market policies for organic rice, with a focus on prioritizing farmer justice and fair pricing management for farmers.